Improving the Electronic Properties of Au/n-Si Type Schottky Junction Structure With Graphene-PVP Nano-Thin Film by Using the I-V, C−2-V and G/ω-V Characteristics - CICEK, Osman (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The letter reports the performance assessment of Au/ n -Si type Schottky Junction Structure (SJS) with and without the graphene-PVP layer, classified as SJS1 and SJS2 devices. The electronic parameters by using the developed LabVIEW based program were calculated from raw data of I-V, C-V and G/ω-V measurements at room temperature. According to Thermionic Emission (TE) theory, the graphene-PVP layer significantly modified the barrier height than the other structure. Using the Ohm's Law, it is found that the $R_{sh}$ magnitude increases, while the $R_{s}$ magnitude decreases for SJS2, according to SJS1 type device. Alternatively, using Cheung's and the modified Norde functions for the accuracy and reliability of the results, the obtained n , $\phi _{Bo}$ , $R_{s}$ values by both equations are in good agreement. Using the C−2-V and G/ω-V characteristics, the magnitudes of the electronic parameters, such as $\phi _{Bo}\,_{{\rm{(C-V)}}}$ , $V_{bi}$ , $V_{D}$ , $N_{D}$ , $E_{F}$ , $R_{s}$ , etc., for the devices were calculated to supply more information. Also, the $C_{i}$ and $C_{ox}$ magnitudes were calculated 1.299 × 10−10 F and 1.192 × 10−10 F at 3 V and then, the interface layer thicknesses were obtained as 2.08 nm and 68.8 nm for SJS1 and SJS2, respectively. It can be concluded that the graphene-PVP layer significantly affects the quality and performance of Au/ n -Si type SJS devices.
Keywords: 7. Clean energy